Chronic social stress in rainbow trout: Does it promote physiological habituation? - Fernandes-de-Castilho, Marisa; Pottinger, Tom G.; Volpato, Gilson Luiz [UNESP] (Academic Press Inc. Elsevier B.V., 2008)
The effect of chronic social stress on growth, energetic substrates and hormones was tested in rainbow trout, Oncorhynchus mykiss. After a 14-day isolation period, the fish were paired for 8 days. In order to expose fish to chronic intermittent social contact during pairing, they were maintained in direct contact with each other during the first day. After that, a black plastic screen partition was introduced in each tank, preventing direct contact between animals. Every day the partition was removed for 30 min, allowing physical interaction between fish. At the end of pairing period, they were isolated again for 13 days. Fish were weighed and blood was sampled frequently during the experiment. Plasma levels of cortisol, growth hormone, glucose, total protein and free amino acids were quantified. Both dominants and subordinates had specific growth rate decreased during the pairing period, but only subordinates increased when the stressor was abolished (dominants: 0.32 +/- 0.21 and 0.24 +/- 0.41, subordinates: -0.77 +/- 0.29 and 0.37 +/- 0.31, respectively). Dominants showed a higher cortisol level one week after pairing condition had been abolished than subordinates (dominants: 56.76 +/- 13.26, subordinates: 31.89 +/- 13.36). We conclude that chronic condition of intermittent social stress represents a stressful condition for animals of both hierarchical ranks and a treatment of one daily short direct contact between conspecifics does not promote habituation in fish, as mentioned for other stressors. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: social stress; chronic stress; stress physiological habituation; fish hormones; cortisol; growth hormone; energetic mobilization; rainbow trout; energetic of stress; hierarchical dominance; Oncorhynchus mykiss